Problematyka podejmowania decyzji w Unii Europejskiej na mocy Traktatu ustanawiającego Konstytucję dla Europy - Tendera-Właszczuk, Helena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The author indicates that the process of enlarging the European Union has led to the necessity of substantial changes in the decision making system and institutional reorganization. The institutional reform has become a prerequisite for further and successful functioning of the EU-25 and, in the future, the European Union with such candidate countries as Bulgaria and Romania. The paper points out that the accession to the European Union gives the member countries' representatives in The Council of the European Union, The European Parliament, The European Commission and other institutions, the power to decide on political, economic and social matters concerning all the EU citizens and states. Therefore, the author discusses the main changes in the position of new member countries in the EU institutions that have been introduced by The Treaty of Nice and the proposals of changes in the European Union institutional system included in the Treaty Establishing a Constitution for Europe. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 378-388